2020
DOI: 10.3390/molecules25194435
|View full text |Cite
|
Sign up to set email alerts
|

Potential Treatment of Breast and Lung Cancer Using Dicoma anomala, an African Medicinal Plant

Abstract: Globally, cancer has been identified as one of the leading causes of death in public health. Its etiology is based on consistent exposure to carcinogenic. Plant-derived anticancer compounds are known to be less toxic to the normal cells and are classified into acetylenic compounds, phenolics, terpenes, and phytosterols. Dicoma anomala is a perennial herb belonging to the family Asteraceae and is widely distributed in Sub-Saharan Africa and used in the treatment of cancer, malaria, fever, diabetes, ulcers, cold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…In particular, breast and lung cancer are treated with D. anomala extract’s anticancer capabilities. 31 Secoisolariciresinol diglucoside, a kind of phytoestrogen lignan found in Linum usitatissimum (flaxseed), is fermented in the large intestine to produce enterolactone and enterodiol. This intellectual metamorphosis has a positive impact on flaxseed’s anticancer properties.…”
Section: Plant Extracts In Breast Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, breast and lung cancer are treated with D. anomala extract’s anticancer capabilities. 31 Secoisolariciresinol diglucoside, a kind of phytoestrogen lignan found in Linum usitatissimum (flaxseed), is fermented in the large intestine to produce enterolactone and enterodiol. This intellectual metamorphosis has a positive impact on flaxseed’s anticancer properties.…”
Section: Plant Extracts In Breast Cancer Treatmentmentioning
confidence: 99%
“…Although numerous in vitro studies have demonstrated the potential of ginseng extract or its active components as effective anticancer agents in BC, it should be noted that the findings are limited to laboratory settings 31 These compounds have shown the ability to modulate signaling pathways associated with inflammation, oxidative stress, angiogenesis, metastasis, and the stem/progenitor-like properties of cancer cells. However, further research and clinical trials are necessary to establish the efficacy and safety of ginseng extract or its active components in the treatment of BC.…”
Section: Plant Extracts In Breast Cancer Treatmentmentioning
confidence: 99%
“…They evaluated these effects in vitro , specifically against MCF-7 breast cancer cells and NF54 parasitic strains [ 57 ]. Additionally, the study also investigated aqueous root extracts from D. anomala to explore their potential in reducing postprandial hyperglycaemia and modulating the activities of carbohydrate-metabolizing enzymes [ 58 , 59 ]. The pharmacological properties of D. anomala have been investigated for their potential in the treatment of various diseases.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Globally, cancer remains the main public health concern. Cancer is denoted by the continued growth and proliferation of cancerous cells [ 1 , 2 ]. According to the GLOBOCAN estimates of 2020 reported by the International Agency for Research on cancer, the incidence rate of cancer was estimated at 19.3 million cases excluding 18.1 million non-melanoma skin cancers, and 10 million cancer-related deaths excluding 9.9 million non-melanoma skin cancers occurred in 2020 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%